Medical drainage of pancreatic pseudocyst - Yusuf UZUN; A. Reşit BEYLER; Hakan BOZKAYA; Necati ÖRMECİ and Kadir BAHAR and Selim KARAYALÇIN and Ali GÖREN and Abdülkadir DÖKMECİ (Turkish Journal of Gastroenterology, 2019)
-